Do Cross-Border Listing Firms Manage Earnings or Seize a Window of Opportunity? - Ndubizu, Gordian A. (The Accounting Review, 2007)
Firms raising new equity capital at cross-listing (IPO) and those crosslisting existing home-country public shares (non-IPO) benefit from earnings that are high when they cross-list on U.S. stock exchanges. IPO firms have greater benefits than non-IPO firms because they receive cash infusion at listing. I find that performance (ROA) and cash flows peak at cross-listing period for all cross-border firms. Using a matched-firm research design to control for industry and performance, the results suggest that both IPO and non-IPO firms time cross-listing when performance is peaking (seize a window of opportunity). Further tests investigate whether IPO and non-IPO firms differ in their incentives to engage in earnings management at the time of cross-listing. The results suggest that both appear to engage in the same level of earnings management at the time of cross-listing. This suggests that incentives to boost earnings to obtain higher cash infusion are not the main motivation for the earnings management observed. Other incentives, such as greater investor recognition could be a stronger motivation.